2020
DOI: 10.1101/2020.08.15.20175844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-6 and IL-10 as predictors of disease severity in COVID-19 patients: results from meta-analysis and regression

Abstract: Objectives: SARS-CoV-2, an infectious agent behind the ongoing COVID-19 pandemic, induces high levels of cytokines in patients contributing to the disease patho-physiology. Nonetheless, exact association and contribution of particular cytokines towards COVID-19 pathology remains poorly understood. This study performed a comprehensive meta-analysis to establish association between induced cytokines and COVID-19 disease severity to help in prognosis and clinical management. Methods: Scientific literature was se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 76 publications
6
36
0
3
Order By: Relevance
“…correlate with increased anti-inflammatory IL-10 cytokine [39]. The cytokine marker IL-10 can possibly be used as a predictor for fast diagnosis of patients with higher risk of COVID-19 disease deterioration during the infection [40,41]. Several gut commensals with known immunomodulatory potential such as Faecalibacterium prausnitzii, Eubacterium rectale and bifidobacteria were under represented in COVID-19 patients and remained low in samples collected up to 30 days after COVID-19 resolution [42].…”
Section: Gut Bacteria and Cytokine Stormmentioning
confidence: 99%
“…correlate with increased anti-inflammatory IL-10 cytokine [39]. The cytokine marker IL-10 can possibly be used as a predictor for fast diagnosis of patients with higher risk of COVID-19 disease deterioration during the infection [40,41]. Several gut commensals with known immunomodulatory potential such as Faecalibacterium prausnitzii, Eubacterium rectale and bifidobacteria were under represented in COVID-19 patients and remained low in samples collected up to 30 days after COVID-19 resolution [42].…”
Section: Gut Bacteria and Cytokine Stormmentioning
confidence: 99%
“…In order to predict severe cases, a score was generated considering IL-10, IL-6, IL-2, and IL-8 blood concentrations. In this classification, severe cases are characterized by high IL-6 and IL-10 levels, both cytokines previously attributed to increase the immunopathogenesis of COVID-19 and predictive value in severe cases (6, 8). In different settings, IL-6 has been associated with oxidative stress, inflammation, endothelial dysfunction, and thrombogenesis (9-12) which are characteristic features of severe COVID-19 cases caused by excessive myeloid cell activation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dhar et al conducted a meta-analysis to understand the correlation between the cytokines overexpressed in COVID-19 patients and disease pathogenesis. The results suggested that two cytokines, IL-6 and IL-10, showed significantly raised levels and could be quantified to estimate the risk and severity of the disease [ 10 ].…”
Section: Introduction To Cytokinesmentioning
confidence: 99%